2021
DOI: 10.3390/su132011553
|View full text |Cite
|
Sign up to set email alerts
|

The Known Unknowns: What Citizen Science Projects in Germany Know about Their Volunteers—And What They Don’t Know

Abstract: The citizen science landscape in Germany offers an enormous range for participation. More than 170 projects currently present themselves on the national citizen science platform. In 2020, we conducted a survey among 140 projects (participation rate 56%), and they provided information on the organisational framework and characteristics (disciplines, initiators, funding, and project goals), as well as on the academic researchers and the volunteering citizen scientists involved. A surprising result was that the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 41 publications
2
16
0
4
Order By: Relevance
“…Analysis of citizen science projects in Germany in the Humanities and Social Science by Göbel et al (2020) showed that people engaged in these projects are predominantly males over 50 years of age, with an academic background. Moczek et al (2021) presented similar findings for citizen science in the…”
Section: Categoriessupporting
confidence: 68%
“…Analysis of citizen science projects in Germany in the Humanities and Social Science by Göbel et al (2020) showed that people engaged in these projects are predominantly males over 50 years of age, with an academic background. Moczek et al (2021) presented similar findings for citizen science in the…”
Section: Categoriessupporting
confidence: 68%
“…Analysis of citizen science projects in Germany in the Humanities and Social Science by Göbel et al (2020) showed that people engaged in these projects are predominantly males over 50 years of age, with an academic background. Moczek et al (2021) presented similar findings for citizen science in the…”
Section: People (Fp)supporting
confidence: 68%
“…Citizen scientists should have been supported with more specific instructions for the recordings, i.e., how (smartphone orientation), where (regions), and when (during the night). Such a task-lead approach facilitates data collection for citizen scientists (Moczek et al 2021 ) and enables them to get a common understanding of data quality (Land-Zandstra et al 2021 ). Positive feedback and confirmation of the number of successfully recorded nightingale songs likewise might have helped to increase quality (Peltola and Arpin 2018 ) and motivate citizen scientists to participate long-term (Pandya and Dibner 2018 ).…”
Section: Discussionmentioning
confidence: 99%